Development of Tumor Mutation Burden-Related Prognostic Model and Novel Biomarker Identification in Stomach Adenocarcinoma - Fu, Min; Huang, Yongbiao; Peng, Xiaohong; Li, Xiaoyu; Luo, Na; Zhu, Wenjun; Yang, Feng; Chen, Ziqi; Ma, Shengling; Zhang, Yuanyuan; Li, Qianxia; Hu, Guangyuan (Frontiers in Cell and Developmental Biology, 2022)
Background: Stomach adenocarcinoma (STAD) is one of the most common tumors. Tumor mutation burden (TMB) has been linked to immunotherapy response. We wanted to see if there was any link between TMB and cancer prognosis. Methods: The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases were used to obtain mutation data, gene expression profiles, and clinical data. We looked at the differences in gene expression and immune markers between low and high TMB groups, built an immune prognostic model, and created a dynamic nomograph App that may be used in the clinic. Simultaneously, We ran the immunotherapy prediction and model comparison at the same time. Finally, model gene mutation and copy number variation (CNV) were displayed. Results: Firstly, basic mutation information and differences in immune infiltration in STAD are revealed. Secondly, the prognostic model developed by us has good accuracy, and the corresponding dynamic nomograph Apps online and immunotherapy prediction facilitate clinical transformation. Furthermore, mutation and CNV of model genes enrich the research contents. Conclusions: Our findings imply that TMB plays a significant role in the prognosis of STAD patients from a biological perspective.